Effect of trypanosomiasis on hematologic characteristics of bream (Abramis brama) - T. B. Lapirova; E. A. Zabotkina (Regulatory Mechanisms in Biosystems, 2018)
Trypanosomes are flagellated protozoa; they parasitize in the blood of a wide range of vertebrates and invertebrates, including fish, for which leeches are carriers. The metabolites released by trypanosomes are toxic to the host, cause disruption of homeostasis, which leads to illness and even death. Parasites in fish living in hot climates are the most common and better studied. Trypanosomes were first detected in common bream (Abramis brama L.) from the Uglich Reservoir (Upper Volga) in August 2015. The aim of this work is to study the effect of these parasites on the hematological parameters of the fish. As a control, blood indices of uninfected fish were used. The condition factor of infected fish did not differ from that of healthy fish. There were no significant differences between the two groups of fish in contents of total serum protein and glycemia. This may indicate a low level of bream parasitemia. At the same time, a significant increase in the leukocyte abundance index was detected, which indirectly indicates an increase in the number of these cells in the infected fish compared with the control ones, statistically significant differences were found in the leukogram: the proportion of eosinophils in the diseased fish increased almost 6 times while the relative number of lymphocytes decreased. The pattern of red blood also changed: the proportion of immature erythrocytes increased in the infected fish; a small number of microcytes and amitoses of erythrocytes and differences in the cytometric characteristics of red blood cells were found. The level of hemoglobin significantly decreased. A sharp increase in the content of circulating immune complexes indicates a shift in antigenic homeostasis caused by the presence of parasites. A similarity in the reaction of a number of indicators of the blood system of bream with trypanosomiasis to that of animals of higher systematic groups was revealed. The interpretation of the results obtained during the study of the effect of parasites on the host organism requires consideration of its physiological status and habitat conditions, the stage of the disease and the mechanism of adaptation of the parasite to the host defense system.